Improving resveratrol bioavailability using water-in-oil-in-water (W/O/W) emulsion: Physicochemical stability, in vitro digestion resistivity and transport properties. (December 2021) - Shi, Aimin; Wang, Jun; Guo, Rui; Feng, Xinyue; Ge, Yanzhen; Liu, Hongzhi; Agyei, Dominic; Wang, Qiang
Graphical abstract: Highlights: Novel W/O/W multiple emulsion for delivering of resveratrol was built. W/O/W multiple emulsion showed excellent stability under different pH, temperature and long-time storaging. W/O/W multiple emulsion reflected a good resistance to peristalsis and digestive juices until the intestine. The transport of resveratrol in W/O/W multiple emulsion across Caco-2 monolayer cell was passive diffusion. W/O/W multiple emulsion shown potential ability to improve the bioavailability of resveratrol. Abstract: Evaluations have been made about the physicochemical stability in water-in-oil-in-water (W/O/W) emulsion loaded with resveratrol under different pH, NaCl concentration, temperature, and storage time. The in vitro digestion and Caco-2 cell transport were also investigated. Results showed W/O/W emulsion remained stable at pH 2–8, temperatures of 25–70 °C and could be stable storage for 77 days. With an increase in NaCl concentration from 1 to 500 mM, the zeta potential changed from −40 mV to −10 mV, but the droplets size didn't show any significant change. The in vitro digestion showed W/O/W emulsion could maintain the structure until small intestine which could give higher protecting for resveratrol. Meanwhile, W/O/W emulsion could reduce the efflux rate of resveratrol across the Caco-2 cell monolayers and special complex of W/O/W emulsion could delay resveratrol release. Results indicated that W/O/W emulsion was suitable vehicle for resveratrol and could improve its bioavailability considering those complicated influence factors.